COMPARATIVE ANALYSIS OF STATE AND NON-STATE PENSION PROVISION SYSTEMS: ADMINISTRATIVE AND LEGAL ASPECT - Кондрат, Людмила Геннадіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: comparative analysis of state and non-state pension provision systems, which will allow determining the features of managerial influence on these two systems. Research methods: analysis, synthesis, generalization, comparison, etc. Results: the specifics of the functioning of state and non-state pension provision systems through their comparison and the need to distinguish between means and methods of administrative and legal regulation of these two systems have been established. Discussion: enshrining in the legislation on the regulation of the non-state pension provision system of such methods and means of administrative and legal regulation that will positively impact the efficiency and transparency of the system operation, but will not affect its operational independence. The central element of the system of the social protection for the public in any developed country is pension provision. Non-state pension funds in many developed countries have proven the need and high efficiency of supplementary pension provision on a private basis. However, in Ukraine they have not gained popularity due to ineffective administrative and legal regulation by the state. The purpose of the non-state pension provision system is to enable employees to make additional pension savings and receive larger pension payments through pension savings and investment income from their placement. This brings us to the conclusion that each of the systems of state and non-state pension provision has its own special entities and functioning mechanisms. At the same time, the goals and general principles are similar, and are aimed at preserving and increasing the funds of individuals. However, a distinctive principle of the non-state pension provision system is a voluntary participation of the entities of this system, which determines its independence. The state, conducting administrative and legal regulation of this system through state bodies, must ensure such conditions for the functioning of the non-state pension provision system that will not affect its independence. In such a case, they will positively impact the efficiency and transparency of this system. This research in the course of its further study and analysis will determine the features of the levers of administrative and legal regulation and influence as a direction of administrative and legal science.